Stock Market in Ukraine: modern trends and problems of development - Furdychko, Lubov; Yurkiv, Khrystyna (Видавництво Львівської політехніки, 2013)
The stock market current state analysis on the grounds of the National Commission on Securities and Stock Exchange for the last three years is presented. Several specific problems and prospects of its further development are examined.
Keywords: stock market; securities; stock contracts; stock lists; trade organisers; state regulator